A Review of Risk Factors and Predictors for Hemorrhagic Transformation in Patients with Acute Ischemic Stroke - Sneha E. Thomas; Noorine Plumber; Priyanka Venkatapathappa; Vasavi Gorantla (International Journal of Vascular Medicine)
Acute ischemic strokes (AIS) and hemorrhagic strokes lead to disabling neuropsychiatric and cognitive deficits. A serious and fatal complication of AIS is the occurrence of hemorrhagic transformation (HT). HT is cerebral bleeding that occurs after an ischemic event in the infarcted areas. This review summarises how specific risk factors such as demographic factors like age, gender, and race/ethnicity, comorbidities including essential hypertension, atrial fibrillation, diabetes mellitus, congestive heart failure, and ischemic heart disease along with predictors like higher NIHSS score, larger infarction size, cardioembolic strokes, systolic blood pressure/pulse pressure variability, higher plasma glucose levels, and higher body temperature during ischemic event, lower low-density lipoprotein and total cholesterol, early ischemic changes on imaging modalities, and some rare causes make an individual more susceptible to developing HT. We also discuss few other risk factors such as the role of blood-brain barrier, increased arterial stiffness, and globulin levels in patients postreperfusion using thrombolysis and mechanical thrombectomy. In addition, we discuss the implications of dual antiplatelet therapy and the length of treatment in reference to the incidence of developing HT. Current research into inflammatory mediators and biomarkers such as Cyclooxygenase-2, matrix metalloproteinases, and soluble ST2 and their potential role as treatment options for HT is also briefly discussed. Finally, this review calls for more research into use of dual antiplatelet and the timing of antiplatelet and anticoagulant use in reference to hemorrhagic transformation.